Reflections on the significance of the relationship between mind and body in medicine - Boey, Christopher Chiong Meng (2010)
In the last three centuries, medicine has focused predominantly on the physical body as the source of disease, placing very little importance on the mind. However, the significance of mind-body interactions in medicine is now increasingly being recognised. True health must include both the physical body and the mind. This article traces our concepts of the relationship between mind and body since primitive times and explores its relevance to the maintenance of health. (JUMMEC 2010; 13(1): 3-11)